Ensuring Indigenous People's Rights Protection Through Normative Law in Land Acquisition for Indonesia's New National Capital City, Nusantara - Permadi, Iwan; Dungga, Weny Almoravid; Arshad, Azhani (Universitas Negeri Gorontalo, 2025)
The development of Indonesia's new capital, Ibu Kota Nusantara (IKN) or the Nusantara Capital City, involves land acquisition, potentially impacting the rights of indigenous peoples. This study evaluates the effectiveness of normative law in protecting these rights during the land acquisition process. Using a normative method, it examines relevant laws, regulations, jurisprudence, and academic literature through qualitative analysis. The findings reveal that while a robust legal framework exists to protect indigenous rights, implementation challenges persist. Key issues include determining fair compensation, land ownership recognition, relocation, and cultural preservation. Addressing these problems requires improved synergy and refinement of laws and regulations. The study highlights the critical need to bridge the gap between normative legal provisions and real-world practices. It emphasizes a holistic approach involving the government, indigenous communities, and stakeholders to achieve equitable and sustainable development. By offering operational legal solutions, the research underscores the importance of consistent legal application to respect indigenous rights. The findings call for multidisciplinary studies to tackle the complexities of protecting indigenous peoples in large-scale development projects. Strengthening legal mechanisms and fostering inclusive collaboration are essential for ensuring development aligns with the rights and needs of indigenous communities.